An Alternative, Banana Peel-Based Medium Used to Investigate the Catalytic Properties of Peroxidase from a Fungus, Inonotus Sp sp2 Recently Isolated in Southern Chile - Contreras-Villacura, E; Urra-Hernandez, J; Vasquez-Perez, O (2012)
Recycling industrial wastes is one of the major goals of bioengineering research. Agricultural wastes are often rich in natural sources of organic and inorganic compounds. The present study investigates the use of banana peel waste as a non-conventional alternative to nitrogen-enriched glucose media for a white rot fungus (WRF), Inonotus sp. SP2, recently isolated in southern Chile. WRF are known to produce biodegrading enzymes, such as peroxidases, that can have industrial and biotechnological applications. To that end, the metabolic characteristics and catalytic properties of peroxidases produced by Inonotus sp. SP2 were compared between glucose and banana peel-based growth mediums. The results establish that this strain of WRF produces high concentrations of a Mn+2-dependent peroxidase, with greater enzymatic activity in extracellular fluid and crude enzyme extracted from fungus grown in banana peel and glucose media, respectively. H2O2 has an inhibiting effect that is greater for enzymes produced in glucose media, and greater biomass can be obtained in banana-peel based media. This demonstrates that banana peel is a suitable and more cost-effective alternative to conventional glucose-based media for the production of biodegradative enzymes, such as peroxidase. Unlike other strains of WRF, the metabolic characteristics of Inonotus sp. SP2 demonstrate that it enters secondary metabolism with the production oxidative enzymes after both carbon and nitrogen sources are depleted. This suggests that with further investigation, this strain of WRF may be useful in industrial applications that require the biodegradation of nitrogen and carbon-based wastes and recalcitrant compounds. © The Korean Society for Biotechnology and Bioengineering and Springer 2012.